2020
DOI: 10.1097/sla.0000000000004613
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Genomic Profiles are Associated With Conversion to Resection and Survival in Patients With Initially Unresectable Colorectal Liver Metastases Treated With Systemic and Hepatic Artery Chemotherapy

Abstract: Objective: To examine genomic correlates of conversion to resection (CTR and overall survival (OS) in patients with initially unresectable colorectal liver metastasis (IU-CRLM) treated with combination systemic and hepatic artery infusion (HAI) chemotherapy. Background: In patients presenting with IU-CRLM, combination systemic and HAI chemotherapy enables CTR with associated long-term OS in a subset of patients. Genomic correlates of CTR and OS in IU-CRLM have not been previously explored. Methods: Specime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…In a study that used hepatic arterial infusion for unresectable CRC liver metastases. Datta et al reported conversion rates of 45% in RAS and BRAF wt ± TP53 mt, 45% in RAS mt + TP53 wt, 39% in RAS mt + TP53 mt, and no conversions for BRAF mt patients [ 28 ]. Further, a conversion rate of 22% for RAS wt was observed in the FIRE-3 trial [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a study that used hepatic arterial infusion for unresectable CRC liver metastases. Datta et al reported conversion rates of 45% in RAS and BRAF wt ± TP53 mt, 45% in RAS mt + TP53 wt, 39% in RAS mt + TP53 mt, and no conversions for BRAF mt patients [ 28 ]. Further, a conversion rate of 22% for RAS wt was observed in the FIRE-3 trial [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…[26][27][28][29] The focus of much current controversy is on the management of patients with colorectal cancer and potentially resectable liver metastases -this is the cohort of the CoSMIC study. [30][31][32][33] Avoiding over-interpretation of these data, several points emerge. First, the study confirms that even in this selected referral population, those who do not or cannot undergo surgery, typically because of a combination of age, co-morbidity and tumor size have a less favourable outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Leveraging this methodology, our group has focused on the genomic co-occurrence of KRAS and TP53 alterations as a prototype of this paradigm. Utilizing this extreme-outlier methodology, we have identified the association between KRAS-TP53 co-alteration and a clinical phenotype defined by chemoresistance [3], aggressive non-salvageable metastatic proclivity [4, 5], and worse cancer-related survival compared with KRAS or TP53 alterations alone [4] in non-PDAC GI cancers. Moreover, we and others have linked KRAS-TP53 co-alteration with the disproportionate enrichment of innate immune populations and immunoregulatory signaling in these GI cancers, implicating KRAS-TP53 cooperativity a model to investigate innate immune regulation [7].…”
Section: Introductionmentioning
confidence: 99%